2022
DOI: 10.3389/fmicb.2022.989272
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community composition in the rhizosphere of Pteris vittata and its effects on arsenic phytoremediation under a natural arsenic contamination gradient

Abstract: Arsenic contamination causes numerous health problems for humans and wildlife via bioaccumulation in the food chain. Phytoremediation of arsenic-contaminated soils with the model arsenic hyperaccumulator Pteris vittata provides a promising way to reduce the risk, in which the growth and arsenic absorption ability of plants and the biotransformation of soil arsenic may be greatly affected by rhizosphere microorganisms. However, the microbial community composition in the rhizosphere of P. vittata and its functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that As contamination can significantly reduce soil microbial biomass nitrogen and microbial biomass carbon, which are important sources of soil nitrogen and organic carbon ( Ghosh et al, 2004 ). In addition, a large number of studies have confirmed that soil As pollution reduces soil biodiversity ( Yu et al, 2021 ; Jia et al, 2022 ) and then affects the cycling of C, N, and other elements in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that As contamination can significantly reduce soil microbial biomass nitrogen and microbial biomass carbon, which are important sources of soil nitrogen and organic carbon ( Ghosh et al, 2004 ). In addition, a large number of studies have confirmed that soil As pollution reduces soil biodiversity ( Yu et al, 2021 ; Jia et al, 2022 ) and then affects the cycling of C, N, and other elements in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…However, the interactions of soil microbiomes and plants in metal(oid)s remediation are poorly understood and explained, notably in the case of As. For example, a reduced natural microbiota was confirmed in the As-contaminated rhizosphere, with a gradual enrichment of microbial genes involved in As(III) oxidation, As(V) reduction and As (de)methylation in the rhizosphere, following increased As uptake by the hyperaccumulator Pteris vittata [ 101 ]. In the study by [ 102 ], the arsM gene was found to be abundant in the roots and rhizosphere of rice, suggesting that methylated As accumulated in rice may be the result of horizontal gene transfer from the soil microbiota.…”
Section: Interaction Of the Rhizosphere Microbial Community On The Ph...mentioning
confidence: 99%